Digital empowerment on hold: DiGA adoption gaps−a German national cross-sectional patient survey study - Kremer, Phillip; Fink, Daniel; Morf, Harriet; Labinsky, Hannah; Gente, Karolina; Aries, Peer; Krusche, Martin; Muehlensiepen, Felix; Kuhn, Sebastian; Hueber, Axel; Knitza, Johannes (Rheumatology international, 2025)
Digital health applications (DiGAs), prescribable and reimbursed in Germany since 2020, have the potential to enhance patient self-management. This study aimed to assess rheumatology patients’ awareness, willingness to use, suitability, and actual adoption of DiGAs. Between February 17 and April 8, 2025, adult patients attending seven German rheumatology outpatient clinics completed an electronic survey. A total of 246 patients participated (mean age 50.4 years; 71.1% female), with most treated at university hospitals (59.8%). The predominant diagnoses were rheumatoid arthritis (41.1%), psoriatic arthritis (18.3%), and axial spondyloarthritis (10.2%). While only 19.5% reported prior use of medical apps, 39.8% were aware of DiGAs, and 12.6% had used one. Notably, 84.6% reported at least one comorbidity matching an approved DiGA indication, most commonly back pain (54.8%), chronic pain (52.0%), and sleep disorders (35.8%). A majority expressed willingness to regularly use a DiGA (72.4%) and were open to recommendations from their rheumatologists or health insurers (72.8%). Additionally, 76.0% showed interest in a rheumatology-specific DiGA. Despite high interest and relevant comorbidities among patients, current DiGA use was limited. These findings underscore the need for targeted implementation strategies to increase uptake and realize the full potential of digital health applications in rheumatology care. The results also emphasize the need for rheumatologists to actively educate and guide their patients regarding the availability and potential benefits of DiGAs.